Green Banana Flour Technology: from Raw Material to Sensory Acceptance of Products Made with Green Banana Flour in the Brazilian Scenario - Cândido, Hebert Teixeira [UNESP]; Marzullo, Yasmine Ohanna Toledo [UNESP]; Leonel, Magali [UNESP] (FapUNIFESP (SciELO), 2023)
Brazil is a major producer of bananas, being the world's fourth-largest producer. The fruit is a source of minerals and vitamins and, when green, has a high content of resistant starch. Among the possibilities of processing, green banana flour has gained prominence due to its physical, nutritional, and functional characteristics, which can be used for the making of different food products. However, the raw material and the processing steps can influence these characteristics. Thus, this study aimed to provide information ranging from the choice of raw material to the sensory acceptance of consumers. The present work discussed the influence of ripening on fruit characteristics, processing stages and flour characteristics as a result of the different used fruits part or cultivar/variety of banana, and the possibilities of products with good technological quality and sensory acceptance of products made with green bananas flours by Brazilian consumers. One of the main differences provided by the cultivar is the flour yield, which is higher in banana cultivars with lower moisture content and selected for frying. There is little information regarding the whole green banana flour, which could reduce waste and contribute nutritionally to preparations. New products having green banana flours as an ingredient show wide possibilities for a partial or total replacement to other flours, as well as good sensory acceptance, which has led to a growing interest in banana processing and its growing market.
Keywords: Banana processing; Functional food; Green banana flour